2022
DOI: 10.1039/d2fo00525e
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide mononucleotide supplementation protects the intestinal function in aging mice and d-galactose induced senescent cells

Abstract: Aging is concomitant with the decline of various physiological functions. Nicotinamide mononucleotide (NMN) is an important precursor of nicotinamide adenine dinucleotide (NAD+) that shows potential to retard aging. Herein, we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…The relative levels of gene expression were normalized with β-actin as a housekeeping gene and then calculated using the comparative CT method (2 −ΔΔCt ) as shown in our previous study. 20…”
Section: Methodsmentioning
confidence: 99%
“…The relative levels of gene expression were normalized with β-actin as a housekeeping gene and then calculated using the comparative CT method (2 −ΔΔCt ) as shown in our previous study. 20…”
Section: Methodsmentioning
confidence: 99%
“…We found that NMN supplementation restored the nuclear transfer of Nrf2 and effectively upregulated the expression of these antioxidant genes. Recent studies have also shown that NMN can upregulate the expression of Nrf2 and enhance the antioxidant ability of intestinal cells [ 39 ]. These results suggest that the protective effect of NMN against oxidative stress is regulated by Nrf2.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota analyses mainly followed the methods described in previous studies. 18,19 The total genomic DNA (gDNA) of each colonic content sample was extracted using a QIAamp DNA isolation kit (Qiagen, Hilden, Germany). The concentration and the integrity of the isolated gDNA were assessed using a Nanodrop 2000 (TermoFisher Scientific, USA) and 1.5% agarose gel electrophoresis, respectively.…”
Section: Gut Microbiota Analysismentioning
confidence: 99%